Culture-Led Regeneration in Rome: From the Factory City to the Knowledge City - Palazzo, Anna Laura (International Studies. Interdisciplinary Political and Cultural Journal, 2017)
In the early 1990s, the notion of culture-led regeneration entered the urban agenda of several European cities confronted with drastic economic changes due to losses in their industrial base. This paper critically addresses a major case in the City of Rome, indeed less affected by these phenomena. In here, the densely populated working-class districts of Ostiense and Testaccio along the Tiber River just outside the City Centre have become part for some years now of a culture-led regeneration program conveying a brand new idea of “Knowledge City” deemed able to supplant the previous image of the “Factory City.”